Factors influencing the utilization of breast cancer screening services in Korean women using Andersen’s behavioral model - Park, Hyejin (International Journal Of Community Medicine And Public Health, 2024)
Background: Breast cancer is a major health concern worldwide, and timely screening plays an important role in early detection and improved treatment outcomes. In this study, factors influencing the utilization of breast cancer screening services were examined using Andersen’s behavioral model, which is widely known as a framework for research on health services utilization. Methods: In this cross-sectional study, data from 2,602 women aged 35 and older were analysed. Results: The results of this study shown that the utilization of breast cancer screening was significantly related to predisposing factors, including age and marital status. Moreover, enabling factors, such as income, were also found to be related to screening utilization. However, need factors, such as perceived health status and limitation of activity, did not show a significant association with the utilization of breast cancer screening services. Conclusions: This study identified factors significantly associated with the utilization of breast cancer screening among Korean women. The findings of this study will contribute to better understand the factors influencing the utilization of breast cancer screening and the development of policies for breast cancer prevention.